2016
DOI: 10.1039/c6nr06387j
|View full text |Cite
|
Sign up to set email alerts
|

Role of shape in substrate-induced plasmonic shift and mode uncovering on gold nanocrystals

Abstract: A number of plasmonic devices and applications, such as chemical and biological sensors, plasmon-enhanced solar cells, optical nanoantennas, metamaterials and metasurfaces, require the deposition of plasmonic metal nanocrystals on various substrates. Because the localized plasmon resonance modes, energies and strengths are strongly dependent on the dielectric function of the surrounding environment, the substrate is expected to largely affect the plasmonic properties of supported metal nanocrystals. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 64 publications
2
60
0
2
Order By: Relevance
“…However it was shown that for large enough particles, strong diffractive coupling can occur even in an asymmetric configuration 29 , 57 , 58 . Furthermore, additional peaks at the blue side of the original resonance can arise 59 61 . We first consider the cavity resonances for a FP cavity that is partially filled with glass (SiO 2 ) of refractive index of 1.45.…”
Section: Structure and Designmentioning
confidence: 99%
“…However it was shown that for large enough particles, strong diffractive coupling can occur even in an asymmetric configuration 29 , 57 , 58 . Furthermore, additional peaks at the blue side of the original resonance can arise 59 61 . We first consider the cavity resonances for a FP cavity that is partially filled with glass (SiO 2 ) of refractive index of 1.45.…”
Section: Structure and Designmentioning
confidence: 99%
“…It was reported previously that the asymmetry of the environment may cause hybridization of the plasmonic modes of the nanoparticle if their spectral positions are close [23]. This effect was studied for different metallic nanoparticles [23][24][25][26][27], however the possible modulation of the optical properties due to the CTAB layer around the nanoparticles was not considered. Also, important to note that in majority of studies the optical properties of the metallic nanospheres are simulated using Mie theory and effective refractive index approximation which does not include all mentioned effects.…”
Section: Introductionmentioning
confidence: 99%
“…Однако такой способ требует прозрачной подложки, например кварца, сапфира или стекла. Действительно, большинство работ, исследующих ЛППР, представляют результаты для металлических нанокластеров, размещенных на прозрачной подложке, например [12; 13], только немногие имеют дело с непрозрачным материалом подложки, таким как кремний [14][15][16][17][18]. Определение частотного положения ЛППР для плазмонных структур на непрозрачных подложках является непростой задачей из-за сложности разделения излучения рассеянного плазмонами и обратного отражения от подложки [19].…”
Section: Introductionunclassified
“…Максимумы в расчетных спектрах поглощения плазмонных образцов использованы для определения энергий ЛППР в массивах нанокластеров Au на непрозрачных подложках. Наши результаты согласуются с литературными данными, полученными ранее альтернативными методами для нанокластеров Au идентичной формы на различных подложках [11][12][13][14][15][16][17].…”
Section: Introductionunclassified